2011
DOI: 10.7202/1001782ar
|View full text |Cite
|
Sign up to set email alerts
|

Trajectoires déviantes et trajectoires de rétablissement à l’adolescence : typologie et leviers d’intervention

Abstract: Les 50 ans de l'École de criminologie Volume 43, numéro 2, automne 2010 URI : id.erudit.org/iderudit/1001782ar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
1
0
4
Order By: Relevance
“…Other studies have also shown that individuals prosecuted most often exhibit poorer outcomes in terms of addiction recovery (Clingempeel, Britt, & Henggeler, 2008;Lennings, Kenny, & Nelson, 2006;Smith, Chamberlain, & Eddy, 2010). Therefore, interventions for these individuals should attempt to reduce both drug use and delinquency (Brunelle & Bertrand, 2010;Turan & Yargic, 2012). Increased severity of psychological problems in youth is associated with a higher level of problematic drug use upon entry into treatment (see also Hawkins, 2009;Schütz & Young, 2009;Stewart, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown that individuals prosecuted most often exhibit poorer outcomes in terms of addiction recovery (Clingempeel, Britt, & Henggeler, 2008;Lennings, Kenny, & Nelson, 2006;Smith, Chamberlain, & Eddy, 2010). Therefore, interventions for these individuals should attempt to reduce both drug use and delinquency (Brunelle & Bertrand, 2010;Turan & Yargic, 2012). Increased severity of psychological problems in youth is associated with a higher level of problematic drug use upon entry into treatment (see also Hawkins, 2009;Schütz & Young, 2009;Stewart, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This thematic analysis was combined with a trajectory analysis of the music and PS use timelines, to understand how music contributes to changes in the addictive trajectory over time, both in beneficial and harmful manners (Brunelle & Bertrand, 2010). To do so, we identified participants’ significant life events and put them in relation with their engagement in music-related activities.…”
Section: Methodsunclassified
“…Plusieurs articles parus dans la revue vont d'ailleurs adhérer à ce modèle d'intervention, que ce soit auprès des délinquants sexuels (Pellerin et al, 1996 ;Proulx, Aubut, Perron et McKibben, 1994 ;Viens, Tourigny, Lagueux et Étienne, 2012), des jeunes en difficulté (Lanctôt, 2010) ou de la population correctionnelle plus générale (Cortoni et Lafortune, 2009 ;Lafortune et Blanchard, 2010). Un second modèle d'intervention, soit l'approche développementale, devient aussi très populaire, en particulier auprès des jeunes en difficulté (Brunelle et Bertrand, 2010 ;Carbonneau, 2008 ;Dionne, 1996 ;Le Blanc, 2010 ;Tarabulsy, Robitaille, Lacharité, Deslandes et Coderre, 1998). Ces deux modèles bénéficieront d'une très large diffusion au Québec, tant auprès des chercheurs que des intervenants.…”
Section: Prise En Charge Thérapeutique Et Modèles D'interventionunclassified